Nintedanib, a triple angiokinase inhibitor, enhances cytotoxic therapy response in pancreatic cancer. Issue 1 (1st March 2015) - Awasthi, Niranjan; Hinz, Stefan; Brekken, Rolf A.; Schwarz, Margaret A.; Schwarz, Roderich E.
Highlights Nintedanib, a triple angiokinase inhibitor, was evaluated in pancreatic cancer. It inhibited in vitro proliferation of PDAC cells and blocked PI3K/MAPK activity. Nintedanib inhibited local tumor growth and enhanced gemcitabine response. Nintedanib therapy increased animal survival and enhanced gemcitabine response. Nintedanib-controlled mechanisms are potential targets for improved PDAC therapy.